MENUMBUHKAN KARAKTER KEWIRAUSAHAAN PESERTA BELAJAR DI PUSAT KEGIATAN BELAJAR MENGAJAR (PKBM) AL KAHFI BATURAJA - Angga Wibowo Gultom; Yudi Tusri; Anton Kurniawan; Muznah Muznah (Universitas Bina Bangsa, 2021)
Entrepreneurs having significant contribution in creating job opportunities, reducing unemployment, increasing people's income and contributing greatly to the country's economic cycle. For this reason, the government through the Ministry of Education program issued an entrepreneurial skills program to encourage of new entrepreneurs for productive age who do not have a job and are not currently studying. This community service activity aims to prepare mindsets, motivation and strong reasons for 20 participants in the entrepreneurial skills program at PKMB Alkahfi in order to be ready to become new entrepreneurs. The methods used are presentation, focus group discussion, questions and answer, discussion, game and roleplay. The results of this community service show that all participants have a new mindset, understand the character of entrepreneurship, succeed in destroying mental blocks and have high motivation to become new entrepreneurs